Dorobek naukowo-badawczy i wydawniczy Biblioteki Głównej Politechniki Łódzkiej w latach 1945-2005 - Sójkowska , Iwona (Acta Universitatis Lodziensis. Folia Librorum, 2009)
60 years of scientific and research activity as well as the publishing one of the Library of Technical University of Lodz are presented in the following article. The author invokes law regulations concerning academic libraries. She discusses the research activity in the range of drawing up the library subject files, preparing projects of library computerization and collection digitization. She also mentions publications issued by the Library of the Technical University of Lodz, written by the librarians.